ANALISIS USABILITY ADOBE PHOTOSHOP DAN CORELDRAW DALAM PROSES DESAIN GRAFIS MENGGUNAKAN METODE SUS PADA SISWA DKV - Virgie Suciana Kusuma; Ricki Sastra; Mohammad Aris (CV. ADIBA AISHA AMIRA, 2025)
This research aims to determine and compare the usability levels between two graphic design software, namely Adobe Photoshop and CorelDRAW, based on the perceptions of Visual Communication Design students. The research method used is quantitative with a survey approach utilizing the System Usability Scale (SUS) instrument. The research respondents consist of 60 students, with 30 users of Adobe Photoshop and 30 users of CorelDRAW. Data analysis was performed through validity and reliability testing of the instrument. The validity test results indicate that 10 item statements are valid for Adobe Photoshop and 10 valid items for CorelDRAW. The reliability test using Cronbach’s Alpha yielded values of 0.603 for Adobe Photoshop and 0.633 for CorelDRAW. From the Excel testing, the average usability score for Adobe Photoshop is 50.5 and for CorelDRAW is 52.08, both of which fall within the “sufficient” (OK usability) category. Based on the results, it can be concluded that both software have a relatively equal level of usability according to user perception.